2019
DOI: 10.1016/j.clon.2019.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic Biomarkers of Radiation Exposure

Abstract: The keywords 'radiation exposure', 'chromosomal biomarker', 'chromosomal signature', and 'complex chromosome aberrations' were used to search Web of Science and Scopus for peer-reviewed articles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 95 publications
1
20
0
Order By: Relevance
“…In a recent experiment, where lymphocytes of a healthy donor (HD1) were exposed in vitro to alpha particles, we showed that complex aberrations were the most abundant aberration type induced [21], as was expected for high-LET radiation [19]. However, in the present study, no "fingerprint" for high-LET exposure was found in vivo.…”
Section: Cytogenetic Effects Of Radon Spa Therapysupporting
confidence: 39%
See 2 more Smart Citations
“…In a recent experiment, where lymphocytes of a healthy donor (HD1) were exposed in vitro to alpha particles, we showed that complex aberrations were the most abundant aberration type induced [21], as was expected for high-LET radiation [19]. However, in the present study, no "fingerprint" for high-LET exposure was found in vivo.…”
Section: Cytogenetic Effects Of Radon Spa Therapysupporting
confidence: 39%
“…Moreover, the frequency of chromosomal aberrations in peripheral blood lymphocytes is a predictor of human cancer risk [16] and can be used for biodosimetry after a suspected exposure to ionizing radiation [17]. Application of the elaborate mFISH method allowed us to complete a detailed analysis of complex aberrations, which are considered as biomarkers for exposure to densely ionizing (high LET) radiation such as alpha particles [19]. This technique is highly sensitive as all human chromosome pairs are simultaneously labelled by 24 different combinations of fluorescent colors (e.g., [31]).…”
Section: Cytogenetic Effects Of Radon Spa Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…In most organisms, meiotic homolog search is driven by chromosome movements in prophase I in the presence of meiotic DSBs (reviewed in [11,12]). Besides physiological meiotic DSBs, exogenous DSBs (e.g., those resulting from IR) can be toxic, since their (mis)repair may lead to non-homologous or ectopic exchange events involving, at the chromosomal level, translocations and the formation of dicentric and acentric chromosome fragments [13][14][15][16]. Chromosome mobility in the first meiotic prophase is dependent on the cytoskeleton, either on microtubules (S. pombe [17]; mouse [18,19]) or actin (Saccharomyces cerevisiae [20]).…”
Section: Introductionmentioning
confidence: 99%
“…The review by Anderson [6] of cytogenetic markers of radiation exposure is excellent and clearly has a wide application is assessing the effects of radiation exposure, such as following the accidents at Chernobyl and Fukushima. We wonder if the evaluation of residual chromosome damage in peripheral lymphocytes could have a wider application to elucidate the potential carcinogenetic effects of repeated radiological examinations, including those having multiple computed tomography scans, such as patients with stage I testicular cancer.…”
mentioning
confidence: 99%